Pengaruh Aspek Manajemen Keuangan Daerah terhadap Transparansi Pengelolaan Keuangan Daerah Kabupaten Luwuk Timur - Syarah Monika; Muchriana Muchran; Nasrullah Nasrullah (Al-Buhuts, 2023)
This study aims to examine whether the presentation of regional financial reports, accessibility of regional financial reports, and internal control affect the transparency of regional financial management in East Luwu Regency. This study used a type of quantitative research originating from primary and secondary data, by distributing questionnaires to all staff/employees at the East Luwu Regency BKAD office as many as 38 employees. The analytical methods used in this study are validity test, reliability test, classical assumption test, multiple linear regression analysis test, and hypothesis testing with the Coefficient of Determination Test (R2) and t test (Partial Test). The results of this study indicate that: 1) Presentation of regional financial reports has no positive and significant effect on the transparency of regional financial management. 2) The accessibility of regional financial reports has a positive and significant effect on the transparency of regional financial management. 3) Internal control has no positive and significant effect on the transparency of regional financial management.